Penguasaan Kompetensi Pedagogik Guru PAI untuk Meningkatkan Prestasi Siswa pada Mata Pelajaran PAI Kelas XII IPS SMA Negeri 1 Cisarua - Erlyana Febrianti; Nan Rahminawati; Sobar AL-Ghazal (UNISBA Press, 2022)
Abstract. SMA Negeri 1 Cisarua as a favorite school in Bandung Regency has special demands on teachers to be able to improve student achievement. Therefore, pedagogic competence as one of the basic competencies of teachers must be owned by teachers. The objectives of this study were (1) to describe the ability of PAI teachers at SMA Negeri 1 Cisarua in improving student achievement (2) to describe the abilities of PAI teachers at SMA Negeri 1 Cisarua in designing and implementing learning to improve student achievement (3) describing the abilities of PAI teachers at SMA Negeri 1 Cisarua. in designing and implementing learning evaluations to improve student achievement (4) describing the ability of PAI teachers at SMA Negeri 1 Cisarua in developing students' potential to improve student achievement. This research was conducted using qualitative descriptive with content analysis approach. The source of the data obtained is based on the document, namely Permendiknas Number 16 of 2007 concerning Teacher Competence, active observations carried out for 2 times with PAI teacher informants in Class XII IPS and IPA. The results obtained are (1) PAI teachers master pedagogic competence in understanding students, it can be seen in student achievement in academics and character (2) PAI teachers master pedagogic competence in planning and implementing learning, as seen from the increase in student achievement that is conducive and active in participate in direct learning (3) PAI teachers master pedagogic competence in planning and implementing learning evaluations, seen in increasing student achievement, especially in character (4) PAI teachers mastering pedagogic competence in developing student potential, seen in the academic achievements achieved by students, alignment of the learning process with the school's vision, and improvement of student character. Abstrak. SMA Negeri 1 Cisarua sebagai sekolah favorit di Kabupaten Bandung memiliki tuntutan khusus kepada guru-guru untuk dapat meningkatkan prestasi siswa. Oleh karena itu, kompetensi pedagogik sebagai salah satu kompetensi dasar guru wajib dimiliki oleh guru. Tujuan penelitian ini adalah (1) mendeartikelkan kemampuan guru PAI SMA Negeri 1 Cisarua dalam meningkatkan prestasi siswa (2) mendeartikelkan kemampuan guru PAI SMA Negeri 1 Cisarua dalam merancang dan pelaksanaan pembelajaran untuk meningkatkan prestasi siswa (3) mendeartikelkan kemampuan guru PAI SMA Negeri 1 Cisarua dalam merancang dan pelaksanaan evaluasi pembelajaran untuk meningkatkan prestasi siswa (4) mendeartikelkan kemampuan guru PAI SMA Negeri 1 Cisarua dalam mengembangkan potensi siswa untuk meningkatkan prestasi siswa. Penelitian ini dilakukan dengan menggunakan deskriptif kualitatif dengan pendekatan analisis konten. Sumber data yang diperoleh berdasarkan pada dokumen yakni Permendiknas Nomor 16 Tahun 2007 tentang Kompetensi Guru, observasi aktif yang dilakukan selama 2 kali dengan informan guru PAI di Kelas XII IPS dan IPA. Adapun hasil yang diperoleh yaitu (1) guru PAI menguasai kompetensi pedagogik dalam memahami siswa, terlihat pada prestasi siswa dalam akademik dan budi pekerti (2) guru PAI menguasai kompetensi pedagogik dalam merencanakan dan melaksanakan pembelajaran, terlihat dari peningkatan prestasi siswa yaitu kondusif dan aktif dalam mengikuti pembelajaran secara langsung (3) guru PAI menguasai kompetensi pedagogik dalam merencanakan dan melaksanakan evaluasi pembelajaran, terlihat pada peningkatkan prestasi siswa khususnya dala budi pekerti (4) guru PAI menguasai kompetensi pedagogik dalam mengembangkan potensi siswa, terlihat pada prestasi akademik yang diraih oleh siswa, keselarasan proses pembelajaran dengan visi sekolah, dan peningkatan budi pekerti siswa.